Valor de uso, importancia cultural y percepciones sobre mamíferos silvestres medianos y grandes en la Mixteca Poblana - Estrada-Portillo, Deborah Samantha; Rosas-Rosas, Octavio César; Parra-Inzunza, Filemón; Guerrero-Rodríguez, Juan de Dios; Tarango-Arámbula, Luis Antonio (Instituto de Ecología, A.C., 2018)
At the Mixteca Poblana wild mammals are subject to a strong anthropic pressure. The type of research that has been conducted in this region had focused on important game species. That leads to a bias in ecological valuations of the rest of the mammal species in the region, in addition to not considering, in any valuation, the traditional knowledge and needs of the people who take advantage of wildlife. Therefore, it is necessary to know the uses, local knowledge, attitudes and actions about the wild mammals that the population have, through determination of the cultural value and the people willing towards the sustainable use of wild mammals in the study area. The food is the most important use value in the Mixteca with a 49.2% of mention, followed by medicine use (23.7%), trophy (13.7%), amulet (8.2%), decoration (2%), trade (1.1%) and hunting, ritual, clothing, taxidermy and pet (<1%). The most important species for the Mixteca habitants are the white-tailed deer with 9 kinds of uses, the coati with 8, the coyote with 6 and the skunk with 3, but it counts with more number of mentions than the coyote. The species with a higher index of cultural importance (IIC) were the deer, coati, coyote, armadillo, skunk, gray fox and leoncillo. As for the perception that the habitants have about the 12 species of research interest, the coyote and opossum are displeasing, this, despite the coyote being culturally important and widely used. At the Mixteca Poblana, the species that have no use as food obtained low magnitudes of IIC and use value; carnivores (order Carnivora) are considered harmful and are killed to avoid damage at the productive systems. Coyote is a carnivore with the most demand due to the multiple uses that represents and, although it has a high IIC, the negative perception of it coming from myths and fear, forbids it to be a priority species for management and conservation.